"Synthesis Is Not the Same Thing as Uniformity": The Cosmopolitics of Youth Citizenship in Lebanon. Issue 5 (4th October 2021) - Kastrissianakis, Konstantin; Smaira, Dima; Staeheli, Lynn A.
ABSTRACT: By resorting to a single humanity or global citizenship, civil society organisations in Lebanon seek to raise youth above ethno-national and national differences. Youth from different groups, regions or nationalities are pulled-out of their respective milieus and gathered in spaces where they meet, befriend, train and collaborate. While for the duration of workshops and summer camps youth find themselves in a space removed from the many divisions and inequalities so as to see in each other a "shared humanity", they still need to confront those divisions and inequalities that order their everyday lives when they return. In navigating the many contradictions between their lives and the NGO space, sectarianism and global citizenship, young men and women in Lebanon try to carve out a space from which they can engage with the world. By drawing on the notion of cosmopolitics as the extent of one's "world" tied to the political claims one makes in relation to others, this paper will explore how a cosmopolitics of citizenship brings into the fore the politics of global citizenship and its promotion in Lebanon.